Equilibrium fuel supply and carbon credit pricing under market competition and environmental regulations: A California case study. (15th February 2019) - Hu, Kejia; Chen, Yuche
Highlights: Mathematical programming with equilibrium constraints method is used. Investigated simultaneous equilibrium on fuel supply market and carbon trade market. Studied interactions between commodity market and carbon trade market. Cellulosic biofuels play critical role in de-carbonization transport sector. Mathematically and empirically proves the relationship between carbon price and regulation. Abstract: Performance-based environmental regulation has gained popularity as a policy tool to prevent climate change. California implements a Low Carbon Fuel Standard regulation to reduce the average carbon intensity of fuels by 10 percent, without specifying technologies to achieve the target. A carbon trading market is established to facilitate fuel producers making revenue by producing low carbon second-generation renewable fuels. There is a knowledge gap in understanding interactions between commodity and carbon trade markets under performance-based regulation. We propose a mathematical program with an equilibrium constraints model to find the equilibrium transportation energy portfolio under environmental protection policy. The model utilizes Karush-Kuhn-Tucker optimality conditions to represent the profit maximization of fuel suppliers. Profit is counted in both the commodity market and the carbon trading market. Our results show that carbon credit encourages the production of second-generation biofuels, which plays a critical role in the success of the Low Carbon Fuel Standard. Carbon credit price is driven by compliance with carbon intensity regulations, which we prove through mathematical formulation and empirical data analysis. Reducing carbon intensity is the key to promote biobutanol underperformance based on the low carbon fuel policy. The proposed framework, with small adjustments, can be used to evaluate performance-based regulation in other fields.